715 The Importance of Social Media to The Academic Surgical Literature: Relationship Between Twitter Activity and Readership Metrics. (12th October 2021) - Mobarak, S; Stott, M; Lee, W J; Davé, M; Tarazi, M; Macutkiewicz, C
Abstract: Aim: Social media (SoMe) has an increasing role within professional surgical practice, including the publishing and engagement of academic literature. This study aims to analyse the relationship between social media use and traditional and alternative metrics amongst academic surgical journals. Method: Journals were identified through the InCites Journal Citation Reports 2019, and their impact factor (IF), h-index and CiteScore were noted. Social media platforms were examined, and Twitter activity interrogated between 1 st January- 31 st December 2019. Healthcare Social Graph (HSG) score and an aggregated Altmetric score were also calculated for each journal. Statistical analysis was carried out to look at the correlation between traditional metrics, Twitter activity and altmetrics. Results: Journals with higher IF were more likely to use a greater number of SoMe platforms (R 2 =0.648; p < 0.0001). Journals with dedicated Twitter profiles had a higher IF than journals without (median, 2.96 vs 1.88; MWU=390; p < 0.001) however over a one-year period (2018-2019) having a twitter presence did not alter IF (MWU=744.5; p = 0.885). Increased Twitter activity was positively correlated with IF. Longitudinal analysis over six years suggested cumulative tweets correlated with an increased IF (R 2 =0.324, p = 0.004). Novel alternative measures including HSG score (R 2 =0.472, p = 0.005) and Altmetric score (R 2 =0.779, p = 0.001) positively correlated with IF. Conclusions: Higher IF is associated with SoMe presence and activity, particularly on Twitter, with long term activity being of particular importance. Modern alternative metrics correlate with IF. This relationship is complex and future studies should look to understand this further.